Exercise behavior and physical fitness in patients with advanced lung cancer - Titz, Christina; Hummler, Simone; Schmidt, Martina; Thomas, Michael; Steins, Martin; Wiskemann, Joachim (Supportive care in cancer, 2018)
PurposeThe aim of this work was to evaluate exercise behavior and physical fitness of advanced lung cancer patients shortly after primary diagnosis.MethodsBetween November 2013 and December 2016, advanced lung cancer patients (n = 227, mean age 62.2 years) were enrolled shortly after diagnosis and 211 patients were tested for endurance capacity (six-minute walk test) and strength performance (maximum voluntary isometric contraction of upper and lower extremities). Current and previous exercise and walking behavior were assessed using a self-reported questionnaire regarding type, frequency, intensity, and duration. Paired Student’s t tests were used to compare physical fitness to reference data. The relation of potential determinants with physical fitness was assessed using linear regression analysis.ResultsExercise behavior was superior in the year before diagnosis compared to the time of study enrollment. Patients reduced frequency, intensity, and duration of sports/exercise after their lung cancer diagnosis. We observed significantly lower endurance capacity (p < .01) and strength performance in lower extremities (p < .01) in male and female patients compared to age and sex-matched reference data. We found significant correlations of previous exercise and walking behavior with physical fitness shortly after diagnosis in patients with advanced lung cancer.ConclusionPatients with advanced lung cancer showed impaired physical fitness regarding endurance and strength capacity. The strong decline in participation of sports/exercise shortly after diagnosis supports early implementation of physical exercise during anti-cancer treatment.Trial registrationClinicalTrials.gov NCT02055508
Gesehen am 08.08.2019